INHALEd nebulised unfractionated HEParin for the treatment of hospitalised patients with COVID‐19 (INHALE‐HEP): Protocol and statistical analysis plan for an investigator‐initiated international metatrial of randomised studies. Issue 8 (19th January 2021) - van Haren, Frank M.P.; Richardson, Alice; Yoon, Hwan‐Jin; Artigas, Antonio; Laffey, John G.; Dixon, Barry; Smith, Roger; Vilaseca, Alicia B.; Barbera, Ruben A.; Ismail, Tarek I.; Mahrous, Rabab S.; Badr, Mohamed; et al.
Abstract : Aims: Inhaled nebulised unfractionated heparin (UFH) has a strong scientific and biological rationale that warrants urgent investigation of its therapeutic potential in patients with COVID‐19. UFH has antiviral effects and prevents the SARS‐CoV‐2 virus' entry into mammalian cells. In addition, UFH has significant anti‐inflammatory and anticoagulant properties, which limit progression of lung injury and vascular pulmonary thrombosis. Methods: The INHALEd nebulised unfractionated HEParin for the treatment of hospitalised patients with COVID‐19 (INHALE‐HEP) metatrial is a prospective individual patient data analysis of on‐going randomised controlled trials and early phase studies. Individual studies are being conducted in multiple countries. Participating studies randomise adult patients admitted to the hospital with confirmed SARS‐CoV‐2 infection, who do not require immediate mechanical ventilation, to inhaled nebulised UFH or standard care. All studies collect a minimum core dataset. The primary outcome for the metatrial is intubation (or death, for patients who died before intubation) at day 28. The secondary outcomes are oxygenation, clinical worsening and mortality, assessed in time‐to‐event analyses. Individual studies may have additional outcomes. Analysis: We use a Bayesian approach to monitoring, followed by analysing individual patient data, outcomes and adverse events. All analyses will follow the intention‐to‐treat principle, considering all participants in the treatment group to which they were assigned, except for cases lost to follow‐up or withdrawn. Trial registration, ethics and dissemination: The metatrial is registered at ClinicalTrials.gov ID NCT04635241. Each contributing study is individually registered and has received approval of the relevant ethics committee or institutional review board. Results of this study will be shared with the World Health Organisation, published in scientific journals and presented at scientific meetings.